Performance Management Challenges in Multinational Organizations: Global and Local Policy Perspectives - Prihatina Jati; Indri Astuti; Budi Safari; Nurwulan Kusuma Devi (Return : Study of Management, Economic and Bussines, 2023)
Globalization of management is a fact of life. Global management is the performance of management activities that cross national boundaries. Global management helps to solve problems that cannot be solved alone in international cooperation. The growth and development of multinational companies requires quality management. The complexity in handling companies across countries spurs the resources in it to continue to be creative and innovative. The method used in this study is descriptive analytics, by conducting a literature search related to performance management challenges in the context of multinational companies, with a conceptual approach and a historical approach. The results of this study show that management challenges always exist in building a multinational organization, performance management is needed in building a change mentality. To face performance challenges in miltnational organizations there are several steps or strategies that can anticipate them, including: Creating the availability of skilled personnel, Improving the company's ability to adopt and use progress, Building a more effective, efficient, and highly motivated team, which is able to improve the company's competitive position, Ensuring adequate human resources for expansion into new programs. Training, Increased productivity. Reduce employee turnover. Increased efficiency.